Behavioral problems and their relationship to maternal depression, marital relationships, social skills and parenting - Bolsoni-Silva, Alessandra Turini [UNESP] (2020)
Behavioral problems have been associated with multiple variables; however, studies simultaneously investigating parenting practices, marital relationships in bi-parental families, maternal depression, and child behavior remain a gap in the literature. The objective was to verify associations between positive and negative parenting practices, marital relationships, social skills, and behavioral problems among children from bi-parental families with and those without maternal depression; to identify the predictive effect of positive and negative parenting practices, marital relationships, children's social skills, and maternal depression, for internalizing, externalizing behavior problems and internalizing and externalizing comorbidities. A case-control study with a cross-sectional design was adopted to ensure the groups were homogeneous in regard to the children's, mothers', and families' sociodemographic characteristics. A total of 35 mothers currently with depression and 35 without depression indicators participated in the study, while the children were 25 preschoolers and 23 school-aged children. The mothers responded to instruments addressing depression, child behavior, parenting practices, and marital relationships. The results reveal maternal depression associated with marital relationships, positive parenting, and context variables. Maternal depression and marital relationship were found to influence externalizing problems; maternal depression, child-rearing practices, marital relationships, and the children's behavioral repertoires influence internalizing and externalizing comorbidities; and none of the independent variables influenced the occurrence of internalizing problems.